Level of Knowledge of First Aid for Student Injuries at Hidayatullah Islamic Junior High School Martapura - Norlaila Hatiya; Mita Erliana; Aryadi Rachman (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2025)
The aim of this research is to determine the level of first aid knowledge for injuries of students at Hidayatullah Islamic Junior High School Martapura, including: factors regarding the nature of injuries, injury prevention factors and injury treatment factors. The method used in this research is quantitative descriptive research, with data collection instruments using multiple choice tests. The population in this study was students in grades VII, VIII and IX, totaling 79 people. Sampling was carried out using a total sampling technique, a sampling technique where the number of samples is the same as the population. With all Hidayatullah Islamic Junior High School students from classes VII, VII and IX totaling 79 people. The data analysis used is descriptive statistical analysis using the percentage method. Research result; The level of knowledge obtained in First Aid for Injuries of Students at Hidayatullah Islamic Junior High School Martapura is included in the “very poor” category of 13.92% (11 Students), the “insufficient” category of 29.11% (23 Students), the “sufficient” category ” by 21.51% (17 Students), the “good” category was 31.67% (25 Students), the “very good” category was 3.79% (3 Students). Research conclusions: The level of knowledge of first aid for student injuries at Hidayatullah Islamic Junior High School Martapura can be categorized as good